Organizational sensory systems of Polish enterprises in the context of cooperative relationships - Chomicki Michał (Management, 2019)
The aim of this paper is to indicate the relationship between the shape of organizational sensory systems of Polish companies and beneficialness of the shape of cooperative relations between these companies with particular kinds of cooperators. The theoretical part of this article was devoted to the identification of the role of cooperative relations in the contemporary economic environment and a brief description of the concept of organizational sensory system, including its influence on cooperation between companies. The survey used the respondents’ indications of frequency of monitoring of elements of organization and its environment and the indication of the beneficialness of the shape of cooperative relationships with suppliers, customers and co-opetitors (in the framework of coopetitive relations). The chi-squared independence tests were used to demonstrate dependencies. In conclusion, it turned out that there are only two statistically significant relations and both of them pertain to relationships with customers.